Incorporating Inflammation into Mortality Risk in Pediatric Acute Respiratory Distress Syndrome. Issue 5 (May 2017) - Zinter, Matt S.; Orwoll, Benjamin E.; Spicer, Aaron C.; Alkhouli, Mustafa F.; Calfee, Carolyn S.; Matthay, Michael A.; Sapru, Anil
Abstract : Objectives: In pediatric acute respiratory distress syndrome, lung injury is mediated by immune activation and severe inflammation. Therefore, we hypothesized that patients with elevated pro- and anti-inflammatory cytokines would have higher mortality rates and that these biomarkers could improve risk stratification of poor outcomes. Design: Multicenter prospective observational study. Setting: We enrolled patients from five academic PICUs between 2008 and 2015. Patients: Patients were 1 month to 18 years old, used noninvasive or invasive ventilation, and met the American European Consensus Conference definition of acute respiratory distress syndrome. Interventions: Eight proinflammatory and anti-inflammatory cytokines were measured on acute respiratory distress syndrome day 1 and correlated with mortality, ICU morbidity as measured by survivor Pediatric Logistic Organ Dysfunction score, and biomarkers of endothelial injury, including angiopoietin-2, von Willebrand Factor, and soluble thrombomodulin. Measurements and Main Results: We measured biomarker levels in 194 patients, including 38 acute respiratory distress syndrome nonsurvivors. Interleukin-6, interleukin-8, interleukin-10, interleukin-18, and tumor necrosis factor-R2 were each strongly associated with all-cause mortality, multiple markers of ICU morbidity, and endothelial injury. A multiple logistic regression model incorporating oxygenation index, interleukin-8, and tumor necrosis factor-R2 was superior to a model of oxygenation index alone in predicting the composite outcome of mortality or severe morbidity (area under the receiver operating characteristic, 0.77 [0.70–0.83] vs 0.70 [0.62–0.77]; p = 0.042). Conclusions: In pediatric acute respiratory distress syndrome, pro- and anti-inflammatory cytokines are strongly associated with mortality, ICU morbidity, and biochemical evidence of endothelial injury. These cytokines significantly improve the ability of the oxygenation index to discriminate risk of mortality or severe morbidity and may allow for identification and enrollment of high-risk subgroups for future studies. Abstract : Supplemental Digital Content is available in the text.